THE IMPACT OF BANK SIZE ON PROFITABILITYâ€œAN EMPIRICAL STUDY ON LISTED JORDANIAN COMMERCIAL BANKSâ€ - Aladwan, Mohammad Suleiman (European Scientific Journal, ESJ, 2015)
This study is aimed to investigate the effect of bank size on its profitability for Jordanian listed commercial banks within different size bank categories. Data for Jordanian commercial banks for the years from 2007 up to 2012 were used to classify banks for three categories according to their asset size, in respect to their Total Assets. Profitability was measured by Return on Equity (ROE) as dependent variables. The study is constructed to reveal if there is a statistical difference in profitability according to size. Simple regression was applied by using dummy variables for categories to proxy asset size. The results of the study revealed a significance difference in the profitability of these different sized banks.